ANALISIS PREFERENSI, KEPUASAAN DAN LOYALITAS KONSUMEN TERHADAP KERIPIK PISANG DAN SINGKONG DI SENTRA AGROINDUSTRI KERIPIK KOTA BANDAR LAMPUNG - Grace Virginie Agatha; Teguh Endaryanto; Ani Suryani (Lampung University, 2020)
The aims of this research are to analyze consumer’s preferences, satisfaction, and loyalty of banana and cassava chips at chips agroindustry centers in Bandar Lampung. The agro industries were chosen purposively. There were 70 respondents taken by using accidental sampling. Data were collected in May-June 2018 and analyzed descriptively by using Customer Satisfaction Index (CSI) and loyalty pyramid method (switcher buyer, habitual buyer, satisfied buyer, liking the brand buyer, and committed buyer). The results of this research showed that the attributes of banana and cassava chips which become the onsumers preferences were low prices, good taste, crispy texture, pleasant scent, harder to get, and attractive packaging. The satisfaction levels of the consumers of banana and cassava chips were both classified as satisfying and loyal consumers.Key words: banana, cassava, chips, consumers, satisfaction